A latent class approach to investigating farmer demand for biofortified staple food crops in developing countries: The case of high-iron pearl millet in Maharashtra, India - Birol, Ekin; Asare-Marfo, Dorene; Karandikar, Bhushana; Roy, Devesh (International Food Policy Research Institute, 2011)
This study explores farmer acceptance and valuation of a biofortified staple food crop in a developing country prior to its commercialization. We focus on the hypothetical introduction of a high-iron pearl millet variety in Maharashtra, India, where pearl millet is among the most important staple crops. A choice experiment is used to investigate farmer preferences for and trade-offs among various production and consumption attributes of pearl millet.